THE SPIRIT OF WASATIYYAH: SUFISM AND LOCAL WISDOM IN INDONESIA - Hurnawijaya; Apipuddin; Handriawan, Dony (Universitas Islam Negeri Mataram, 2024)
This article explores the spirit of Wasatiyyah within the context of Sufism and local wisdom in Indonesia. Wasatiyyah, which translates to “the middle path” or “moderation,” is a significant concept in Islam that emphasises balance and harmony. Through in-depth study, this article highlights how the principles of Sufism intersect with Indonesia’s local wisdom, creating a unique and inclusive form of religious practice.The study employs a qualitative approach, using ethnographic methods to collect data from various Sufi communities in Indonesia. The findings reveal that the values of moderation within Sufism not only enrich individual spirituality but also strengthen social cohesion and foster tolerance among religious communities. Practices such as dhikr (remembrance of God), tahlil (recitation of the phrase ‘La ilaha illallah’), and religious gatherings commonly conducted by Sufi communities incorporate elements of local wisdom, enriching Indonesia’s spiritual culture. In conclusion, the integration of Sufism and local wisdom in Indonesia gives rise to an adaptive and harmonious religious model. The embodiment of the wasatiyyah spirit in these practices contributes significantly to peace and social harmony in a multicultural society.